Sphingosine 1-phosphate lyase deficiency causes Charcot-Marie-Tooth neuropathy. (7th February 2017) - Atkinson, Derek; Nikodinovic Glumac, Jelena; Asselbergh, Bob; Ermanoska, Biljana; Blocquel, David; Steiner, Regula; Estrada-Cuzcano, Alejandro; Peeters, Kristien; Ooms, Tinne; De Vriendt, Els; Yang, Xiang-Lei; Hornemann, Thorsten; et al.
Abstract : Objective: To identify the unknown genetic cause in a nuclear family with an axonal form of peripheral neuropathy and atypical disease course. Methods: Detailed neurologic, electrophysiologic, and neuropathologic examinations of the patients were performed. Whole exome sequencing of both affected individuals was done. The effect of the identified sequence variations was investigated at cDNA and protein level in patient-derived lymphoblasts. The plasma sphingoid base profile was analyzed. Functional consequences of neuron-specific downregulation of the gene were studied in Drosophila . Results: Both patients present an atypical form of axonal peripheral neuropathy, characterized by acute or subacute onset and episodes of recurrent mononeuropathy. We identified compound heterozygous mutations cosegregating with disease and absent in controls in the SGPL1 gene, encoding sphingosine 1-phosphate lyase (SPL). The p.Ser361* mutation triggers nonsense-mediated mRNA decay. The missense p.Ile184Thr mutation causes partial protein degradation. The plasma levels of sphingosine 1-phosphate and sphingosine/sphinganine ratio were increased in the patients. Neuron-specific downregulation of the Drosophila orthologue impaired the morphology of the neuromuscular junction and caused progressive degeneration of the chemosensory neurons innervating the wing margin bristles. Conclusions: We suggest SPL deficiency as a cause of a distinct form of Charcot-Marie-Tooth disease in humans, thus extending the currently recognized clinical and genetic spectrum of inherited peripheral neuropathies. Our data emphasize the importance of sphingolipid metabolism for neuronal function.